Analisis Perbedaan Pengakuan Pendapatan Menggunakan Metode Kontrak Selesai Dan Metode Persentase Penyelesaian - Alfonsus Herry Susanto; Soedjono Rono (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2016)
Percentage of Completion Method help the company in the financial system of the company in one period may have more than one contract because this method shows the income statement as fair. Revenue recognition with the Percentage of Completion Method using a proper approach to matching concept (compare the costs and revenue appropriately) is the most appropriate method for long term contracts because it can describe the income statement in each period can be reported proportionately and fairly. For short term contracts, companies can use the method of revenue recognition based on the Completed Contract Method or the Percentage of Completion Method with the terms of the contract occurred less than or not more than one accounting period, because if more than one period and using the Completed Contract Method, it can cause report income that is not fair. Keep in mind that the Percentage of Completion Method has the disadvantage that if there is reduction or additional work in a contract, the percentage of work progress to be recalculated, and if there is a change estimated total cost, so the revenue recognized in the previous year must recalculated.